A review of nanoparticle decharging in atmospheric pressure plasma afterglows - Staps , T.J.A. (Frontiers in Physics, 2022)
Plasma afterglows interacting with dust grains present a dynamic environment in which negatively charged dust grains leaving the plasma bulk experience an environment with plasma conditions transient in space and time. This review focuses on the impact of atmospheric pressure on the physics concerning the interaction between dust grains and the plasma afterglow. The four stage model commonly applied to low pressure dusty plasma afterglows provides a guiding framework for the analysis describing the phases of electron temperature relaxation, ambipolar diffusion, ambipolar-to-free diffusion transition and free diffusion. This work is completed by a non-exhaustive overview of research gaps and opportunities in the young and vibrant field of atmospheric pressure dusty plasma afterglows.